Exchange Rate Regimes and Macroeconomic Stability in Central and Eastern Europe - Paul De Grauwe; Gunther Schnabl (Center for Economic Studies and ifo Institute (CESifo), 2004)
This paper explores the impact of the exchange rate regime on inflation and output in the Central and Eastern European (CEE) EU candidate countries. The panel estimations for the period between 1994 and 2002 show that de facto measures of exchange rate stability have a better explanatory power than the de jure measures in the inflation and growth equations. For the whole observation period the estimations reveal a significant impact of exchange rate stability on low inflation as well as a highly significant positive impact of exchange stability on real growth. When sub-dividing the period into a high-inflation period (1994-1997) and a low-inflation period (1998-2002) and when removing outliers from the sample, the evidence in favour of a positive association between exchange rate stability and inflation gets weaker. The association of exchange rate stability with higher real growth remains quite robust. Thus our findings can be interpreted to mean that membership of the CEE countries in the European Monetary Union would have a positive impact on these countries' growth rates.
Keywords: F31; 330; exchange rate regimes; inflation; growth; Central and Eastern Europe; macroeconomic stability